GRAMMAR MASTERY AND WRITING ACHIEVEMENT OF THE TOEFL: A CORRELATIONAL STUDY AT HIGHER EDUCATION - Eka Melati (ELP (Journal of English Language Pedagogy), 2022)
The research was a kind of correlational study which had objective to determine the association of grammar mastery and writing achivement in making prediction how much the correlation among the variables quantitatively. Population of the study was the fourth semester students of AMIK Mitra Gama registered on 2019/2020 academic year totally 126 students, 30 students was the sample of this research taken by cluster sampling technique. Test of grammar and writing adapted from Cambridge Preparation TOEFL was the instrumentation. Data analyzed by using correlation Pearson Product Moment (r-test). The result of the study found that robserved (0,92) is higher than rtable (0,362) on 0,05 significance level. In addition, hypothesis testing resulted that H1 (there is a correlation between grammar mastery and writing achievement) is accepted, but H0 (there is no correlation between gammar mastery and writing achievement of the TOEFL) is rejected. In sum, there was a significant correlation between mastery of grammar and writing achievement for the fourth semester students of AMIK Mitra Gama. From the result of the research, grammar and writing should be stated on lesson plans of English 1, 2 and 3 course and taught more intensive since those skills also support student’s achievement to administer TOEFL.